Comparing short forms of the Social Interaction Anxiety Scale and the Social Phobia Scale - Carleton, R.; Thibodeau, M.; Weeks, J.; Sapach, M.; McEvoy, Peter; Horswill, S.; Heimberg, R. (American Psychological Association, 2014)
The Social Interaction Anxiety Scale (SIAS) and the Social Phobia Scale (SPS; Mattick & Clarke, 1998) are companion scales developed to measure anxiety in social interaction and performance situations, respectively. The measures have strong discriminant and convergent validity; however, their factor structures remain debated, and furthermore, the combined administration length (i.e., 39 items) can be prohibitive for some settings. There have been 4 attempts to assess the factor structures of the scales and reduce the item content: the 14-item Social Interaction Phobia Scale (SIPS; Carleton et al., 2009), the 12-item SIAS-6/SPS-6 (Peters, Sunderland, Andrews, Rapee, & Mattick, 2012), the 21-item abbreviated SIAS/SPS (ASIAS/ASPS; Kupper & Denollet, 2012), and the 12-item Readability SIAS and SPS (RSIAS/RSPS; Fergus, Valentiner, McGrath, Gier-Lonsway, & Kim, 2012). The current study compared the short forms on (a) factor structure, (b) ability to distinguish between clinical and non-clinical populations, (c) sensitivity to change following therapy, and (d) convergent validity with related measures. Participants included 3,607 undergraduate students (55% women) and 283 patients with social anxiety disorder (43% women). Results of confirmatory factor analyses, sensitivity analyses, and correlation analyses support the robust utility of items in the SIPS and the SPS-6 and SIAS-6 relative to the other short forms; furthermore, the SIPS and the SPS-6 and SIAS-6 were also supported by convergent validity analyses within the undergraduate sample. The RSIAS/RSPS and the ASIAS/ASPS were least supported, based on the current results and the principle of parsimony. Accordingly, researchers and clinicians should consider carefully which of the short forms will best suit their needs.